Organizational culture development in improving employee performance at PT. Welling Tapioka Jaya (Research, Society and Development, 2020)
The background of this research is the desire of researchers to find out how the development of organizational culture in improving the performance of employees of PT. Welling Tapioka Jaya. The purpose of this study is to understand and analyze the development of organizational culture in improving employee performance at PT. Welling Tapioka Jaya. The method used in this research is qualitative method. The author uses semi-structured interviews as a data collection technique. The author interviewed 9 people. The research data were analyzed using the Miles and Huberman model consisting of data reduction, data presentation and conclusions. Test the credibility of the data that I use is triangulation of sources. The results showed that the organizational culture adopted at PT. Welling Tapioka Jaya is quite good, this can be seen from employees who work by harmonizing the cultural values ​​of the organization that is in it regardless of whether they like it or not and the employees at PT. Welling Tapioka Jaya respects and values ​​the culture of the organization by following and adapting to the culture within it.